If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(8 + 3n) = 0 (8 * -4 + 3n * -4) = 0 (-32 + -12n) = 0 Solving -32 + -12n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + -12n = 0 + 32 Combine like terms: -32 + 32 = 0 0 + -12n = 0 + 32 -12n = 0 + 32 Combine like terms: 0 + 32 = 32 -12n = 32 Divide each side by '-12'. n = -2.666666667 Simplifying n = -2.666666667
| 0.2t=0.4+0.3t | | 4t+4t= | | 7m-9.4=11.6 | | 1/2t=3.5 | | 5x-(-5x-1)=-8 | | 7x+2=-3+4x+23 | | 11x+2=-24 | | 9v+10=v+9 | | 3.5*2= | | x-19=23 | | 5d+8=53 | | 4x+9-7x=-6 | | 90-x=3/4(180-x)-60 | | 4x+9-7x=-9 | | 0.75=w+2/5 | | (x^2-11)/(2x-1) | | (3/4)x-(7/12)=1 | | 11x-4x=27 | | z/2+1+3/2 | | 3(6x+3)=27 | | 5(2x-4)-(3x+1)=2 | | 9+1/9h=9 | | -6=x/3+4 | | 4x+6+8=3 | | 8(2.4r-3.1s)-6(10-4.3s)= | | x^2+4xy-4y^2-9=0 | | 5+22a=2+10/22 | | 1/4c+2=8 | | 8/4=(6)(0) | | -.2(x+10)-.25(x-4)=x+8 | | 6(X+2)-7=18 | | 0.7t=0.3+0.4t |